2022
DOI: 10.1161/jaha.122.026460
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Function and Arrhythmias in Relation to Small Vessel Disease on Brain MRI: The Multi‐Ethnic Study of Atherosclerosis

Abstract: Background Atrial fibrillation (AF) is associated with increased stroke risk and accelerated cognitive decline, but the association of early manifestations of left atrial (LA) impairment with subclinical changes in brain structure is unclear. We investigated whether abnormal LA structure and function, greater supraventricular ectopy, and intermittent AF are associated with small vessel disease on magnetic resonance imaging of the brain. Methods and Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…A clinical study reported higher microbleed prevalence in patients with atrial fibrillation than in those without, but the analyses were not adjusted for other microbleed risk factors 27 . We previously showed that greater left atrial volume index was associated with microbleeds in MESA participants 20 . Taken together, these findings support the involvement of atrial fibrillation in the pathophysiology of microbleeds, but do not provide insight as to whether atrial fibrillation is causally related to microbleeds or is a manifestation of underlying vascular pathology or shared risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A clinical study reported higher microbleed prevalence in patients with atrial fibrillation than in those without, but the analyses were not adjusted for other microbleed risk factors 27 . We previously showed that greater left atrial volume index was associated with microbleeds in MESA participants 20 . Taken together, these findings support the involvement of atrial fibrillation in the pathophysiology of microbleeds, but do not provide insight as to whether atrial fibrillation is causally related to microbleeds or is a manifestation of underlying vascular pathology or shared risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Microbleeds were initially identified by a deep learning‐based method that used T2‐weighted quantitative susceptibility mapping and SWI images to segment the lesions and differentiate microbleeds from iron deposits (Figure 1). 8 Identified lesions were then reviewed by a radiologist (JBW) who made the final classification, as previously described 20 . Microbleed location was classified by mapping the 146 Multi‐atlas region Segmentation Using Ensembles (MUSE)–based regions of interest 21 to the Microbleed Anatomical Rating Scale (MARS) regions of interest 22 and grouping them into three categories: lobar (frontal, parietal, temporal, occipital, and insula), deep (basal ganglia, thalamus, internal capsule, corpus callosum, and deep and periventricular white matter [WM]), and infratentorial (brainstem and cerebellum).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We worked with the same WML segmentations used in previous SPRINT studies. 26 , 27 , 28 These WML segmentations were derived with a deep learning method 31 and applied in large cohort studies 11 , 32 , 33 , 34 with similar settings. We calculated the total WMLs, mean FA, and MD for all the WM regions of interest (ROIs) of the Type III WM parcellation map.…”
Section: Methodsmentioning
confidence: 99%